Phosphatase-alkaline activity and growth of rice with biological inoculation and micronutrients - Díaz Lezcano, Maura Isabel; Fiori Fernandez, Carlos; Ayala Aguilera, Lider; Yubero, Fatima; Martinez, Roberto; López, Marcelo (Revista Mexicana de Ciencias Agrícolas, 2020)
Inoculation with growth promoting bacteria in crops is an alternative to reduce the use of nitrogen fertilizers and production costs. The objective of this research was to evaluate the effect of inoculating Oryza sativa L. rice seeds with the bacteria Azospirillum brasilense on the enzymatic activity of alkaline phosphatase and its growth. The research was carried out at the Faculty of Agrarian Sciences and the Faculty of Chemical Sciences of the National University of Asuncion, Paraguay. A completely randomized design with five treatments and five repetitions was used. Treatments consisted of T1 (Absolute Control): untreated rice seeds, T2 (Co+Mo): rice seeds treated with cobalt plus molybdenum, T3 (Az): rice seeds inoculated with A. brasilense, T4 (Az+1F): rice seeds inoculated with A. brasilense plus one foliar application of the inoculant and T5 (Az+2F): rice seeds inoculated plus two foliar applications. Anava and Tukey’s test (p
Keywords: Azospirillum brasilense; Oryza sativa L.; enzymatic activity; inoculation